Robotic radiosurgery for temporal bone paragangliomas: single-center experience and review of the literature - Ramos, Sofia (2024)
Objective: To report the experience of a single center in the treatment of temporal bone paragangliomas with Robotic Radiosurgery. Study Design: Single-center retrospective analysis Material and Methods: Between 2017 and 2021, 8 patients with temporal bone paragangliomas were treated with Cyberknife in the Department of Radiation Oncology of Instituto CUF Porto. Results: Half of the patients were diagnosed with recurrent tumors after surgery +/- embolization. The median follow-up was 33 months. Regarding clinical outcomes, 4 patients showed improvement in pre-radiosurgery symptoms, 2 remained symptom-free and 2 demonstrated neurological stability. All tumors revealed regression (n=5) or stable dimension (n=3) during follow-up MRI, with local control of 100%. There was no grade ≥3 or late toxicities. Conclusion: Robotic Radiosurgery seems to be a helpful therapeutic approach in the management of temporal bone paragangliomas, either after surgery and/or embolization recurrences or as a single and radical treatment.